An Analysis of Grammatical Cohesive Device of the Short Story the Little Match Girl by Hans Christian Andersen 2016/2017 - Hidayat, Agus (English Education: Jurnal Tadris Bahasa Inggris, 2016)
The objective of this study is to analyze the grammatical cohesive device especially the reference of a short story written by a famous author, Hans Christian Andersen entitled The Little Match Girl. The type of the study used in this case is descriptive qualitative research. This study is done by analyzing the short story by locating the references used in the story and then calculating the amount of the references and determining the type of references found in to two categories, Anaphoric and cataphoric references. Based on the analysis, it was found that the short story contain 87 (eighty seven) references, in which 81 (eighty one) references belong to the anaphoric category and 6 (six) references belong to cataphoric category.